2019
DOI: 10.3390/v11030288
|View full text |Cite
|
Sign up to set email alerts
|

Function, Architecture, and Biogenesis of Reovirus Replication Neoorganelles

Abstract: Most viruses that replicate in the cytoplasm of host cells form neoorganelles that serve as sites of viral genome replication and particle assembly. These highly specialized structures concentrate viral proteins and nucleic acids, prevent the activation of cell-intrinsic defenses, and coordinate the release of progeny particles. Reoviruses are common pathogens of mammals that have been linked to celiac disease and show promise for oncolytic applications. These viruses form nonenveloped, double-shelled virions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 126 publications
1
20
0
Order By: Relevance
“…Those organelles are referred as viroplasms. They constitute the site of viral genome transcription and replication, as well as the site of packaging of the newly synthesized pregenomic RNA segments into the viral cores [ [75] , [76] , [77] , [78] ]. Viroplasms appear to be spherical and can fuse together [ 79 , 80 ] which indicates that they have liquid properties.…”
Section: Beyond Mnv: Membrane-less Replication Compartments Of Dna Anmentioning
confidence: 99%
“…Those organelles are referred as viroplasms. They constitute the site of viral genome transcription and replication, as well as the site of packaging of the newly synthesized pregenomic RNA segments into the viral cores [ [75] , [76] , [77] , [78] ]. Viroplasms appear to be spherical and can fuse together [ 79 , 80 ] which indicates that they have liquid properties.…”
Section: Beyond Mnv: Membrane-less Replication Compartments Of Dna Anmentioning
confidence: 99%
“…Moreover, in recent years, Tenorio et al (2018Tenorio et al ( , 2019 used light and electron microscopy to demonstrate that reovirus inclusions are membrane-containing structures and that the reovirus σNS and µNS proteins remodel the ER to build neoorganelles for replication. Our results revealed that the depletion of cellular cholesterol inhibited ARV inclusion formation and replication at the post-entry stage in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been established that the virus factories or VIBs utilized by members of the Reoviridae family are responsible for replication and the assembly of virus particles [30][31][32], crucial stages of these processes remain ill-defined. This includes the egress of virus cores from VIBs, and in the context of BTV, their subsequent associating with the outer capsid proteins VP5 and VP2 to generate mature infectious virus particles that are ready for egress from the cell.…”
Section: Discussionmentioning
confidence: 99%